Design and characterization of a single channel two-liquid capacitor and its application to hyperelastic strain sensing1. Issue 5 (7th March 2015) - Liu, Shanliangzi; Sun, Xiaoda; Hildreth, Owen J.; Rykaczewski, Konrad
<x xml:space="preserve">Abstract</x> We show that single channel capacitive strain sensor consisting of a high dielectric constant liquid sandwiched in-between two liquid metal electrodes can have 25 times higher capacitance per sensor's base area when compared to current two-channel liquid metal stain sensors.